hi guys, please solve this question fast :::::
prove that ,
![\tan( \alpha ) + 2 \tan(2 \alpha ) + 4 \cot(4 \alpha ) = \cot( \alpha ) \tan( \alpha ) + 2 \tan(2 \alpha ) + 4 \cot(4 \alpha ) = \cot( \alpha )](https://tex.z-dn.net/?f=+%5Ctan%28+%5Calpha++%29++%2B+2+%5Ctan%282+%5Calpha+%29++%2B+4+%5Ccot%284+%5Calpha+%29++%3D++%5Ccot%28+%5Calpha+%29+)
Answers
Answered by
3
We know that,
Steps:
1)
![\cot( \alpha ) - \tan( \alpha ) \\ = \frac{ \cos( \alpha ) }{ \sin( \alpha ) } - \frac{ \sin( \alpha ) }{ \cos( \alpha ) } \\ = \frac{ {( \cos( \alpha ) ) }^{2} - { (\sin( \alpha ) )}^{2} }{ \sin( \alpha ) \cos( \alpha ) } \times \frac{2}{2} \\ = \frac{2 \cos(2 \alpha ) }{ \sin(2 \alpha ) } = 2 \cot(2 \alpha ) \cot( \alpha ) - \tan( \alpha ) \\ = \frac{ \cos( \alpha ) }{ \sin( \alpha ) } - \frac{ \sin( \alpha ) }{ \cos( \alpha ) } \\ = \frac{ {( \cos( \alpha ) ) }^{2} - { (\sin( \alpha ) )}^{2} }{ \sin( \alpha ) \cos( \alpha ) } \times \frac{2}{2} \\ = \frac{2 \cos(2 \alpha ) }{ \sin(2 \alpha ) } = 2 \cot(2 \alpha )](https://tex.z-dn.net/?f=+%5Ccot%28+%5Calpha+%29++-++%5Ctan%28+%5Calpha+%29++%5C%5C++%3D++%5Cfrac%7B+%5Ccos%28+%5Calpha+%29+%7D%7B+%5Csin%28+%5Calpha+%29+%7D++-++%5Cfrac%7B+%5Csin%28+%5Calpha+%29+%7D%7B+%5Ccos%28+%5Calpha+%29+%7D+%5C%5C++%3D++%5Cfrac%7B+%7B%28+%5Ccos%28+%5Calpha+%29+%29++%7D%5E%7B2%7D+-++%7B+%28%5Csin%28+%5Calpha+%29+%29%7D%5E%7B2%7D++%7D%7B+%5Csin%28+%5Calpha+%29+%5Ccos%28+%5Calpha+%29++%7D+++%5Ctimes++%5Cfrac%7B2%7D%7B2%7D+%5C%5C++%3D++%5Cfrac%7B2+%5Ccos%282+%5Calpha+%29+%7D%7B+%5Csin%282+%5Calpha+%29+%7D++%3D+2+%5Ccot%282+%5Calpha+%29+)
Similarly,
2)
![2 \cot(4 \alpha ) = \cot(2 \alpha ) - \tan(2 \alpha ) \\ - - - (1) 2 \cot(4 \alpha ) = \cot(2 \alpha ) - \tan(2 \alpha ) \\ - - - (1)](https://tex.z-dn.net/?f=2+%5Ccot%284+%5Calpha+%29++%3D++%5Ccot%282+%5Calpha+%29++-++%5Ctan%282+%5Calpha+%29+++%5C%5C++-++-++-+%281%29)
Now, 3)
![\tan( \alpha ) + 2 \tan(2 \alpha ) + 4 \cot(4 \alpha ) \\ = \tan( \alpha ) + 2 \tan(2 \alpha ) + \\ \: \: \: \: 2( \cot(2 \alpha ) - \tan(2 \alpha )) \\ = \tan( \alpha ) + 2 \cot(2 \alpha ) \\ = \tan( \alpha ) + \frac{2}{ \frac{2 \tan( \alpha ) }{1 - {( \tan( \alpha )) }^{2} } } \\ = \tan( \alpha ) + \frac{1 - { (\tan( \alpha ) )}^{2} }{ \tan( \alpha ) } \\ = \tan( \alpha ) + \cot( \alpha ) - \tan( \alpha ) \\ = \cot( \alpha ) \tan( \alpha ) + 2 \tan(2 \alpha ) + 4 \cot(4 \alpha ) \\ = \tan( \alpha ) + 2 \tan(2 \alpha ) + \\ \: \: \: \: 2( \cot(2 \alpha ) - \tan(2 \alpha )) \\ = \tan( \alpha ) + 2 \cot(2 \alpha ) \\ = \tan( \alpha ) + \frac{2}{ \frac{2 \tan( \alpha ) }{1 - {( \tan( \alpha )) }^{2} } } \\ = \tan( \alpha ) + \frac{1 - { (\tan( \alpha ) )}^{2} }{ \tan( \alpha ) } \\ = \tan( \alpha ) + \cot( \alpha ) - \tan( \alpha ) \\ = \cot( \alpha )](https://tex.z-dn.net/?f=+%5Ctan%28+%5Calpha+%29++%2B+2+%5Ctan%282+%5Calpha+%29++%2B+4+%5Ccot%284+%5Calpha+%29++%5C%5C++%3D++%5Ctan%28+%5Calpha+%29++%2B++2+%5Ctan%282+%5Calpha+%29++%2B++%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A+2%28+%5Ccot%282+%5Calpha+%29++-++%5Ctan%282+%5Calpha+%29%29++%5C%5C++%3D++%5Ctan%28+%5Calpha+%29++%2B+2+%5Ccot%282+%5Calpha+%29++%5C%5C++%3D++%5Ctan%28+%5Calpha+%29++%2B++%5Cfrac%7B2%7D%7B+%5Cfrac%7B2+%5Ctan%28+%5Calpha+%29+%7D%7B1+-++%7B%28+%5Ctan%28+%5Calpha+%29%29+%7D%5E%7B2%7D+%7D+%7D++%5C%5C++%3D++%5Ctan%28+%5Calpha+%29++%2B++%5Cfrac%7B1+-++%7B+%28%5Ctan%28+%5Calpha+%29+%29%7D%5E%7B2%7D+%7D%7B+%5Ctan%28+%5Calpha+%29+%7D++%5C%5C++%3D++%5Ctan%28+%5Calpha+%29++%2B++%5Ccot%28+%5Calpha+%29++-++%5Ctan%28+%5Calpha+%29++%5C%5C++%3D++%5Ccot%28+%5Calpha+%29+)
Steps:
1)
Similarly,
2)
Now, 3)
Similar questions
Computer Science,
9 months ago
India Languages,
9 months ago
English,
9 months ago
English,
1 year ago
English,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago
Economy,
1 year ago